Firm and internal environmental factors that affect employee performance in MNCS - Lim, Sze Huey (2023)
This research seeks to determine the firm and internal environmental factors that impact employee performance in multinational corporations. There is a trend that has contributed to the gradual increase of multinational corporations in Malaysia. Yet, research on multinational corporations is scarce, particularly in terms of employee performance. This research can therefore contribute to a deeper knowledge of the elements that influence employee performance in MNCs. The objectives of this research study is to examine the relationship between organisational culture, organisational communications, leaderships style and employee performance in multinational companies (MNCs). Causal and quantitative research design will be used in this research. 200 respondents have completed on the questionnaire as the primary data collection in this research. SPSS Statistics is used as a data analysis tool. Descriptive and inferential analysis including Pearson correlation coefficient and Multiple Regression Analysis are used for data analysis. It is found that organisational culture and organisational communication have a significant relationship with employee performance in MNCs. However, this research found that leadership style has the least impact on employee performance in MNCs.This study assists MNCs’ executives in understanding the elements that influence employee performance and suggests that they should emphasize on organisational culture and communication in order to increase employee performance.